2011
DOI: 10.2106/jbjs.i.00540
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Secondary Prevention of Osteoporosis in Fracture Care: Follow-up to “Own the Bone”

Abstract: The majority of the 1.8 million individuals who sustain a fracture annually in the United States have osteopenia or osteoporosis, yet <15% of these patients subsequently receive treatment for osteoporosis. A prospective cohort study was conducted to assess the effect of two different interventions on the rate of osteoporosis treatment in patients with a fragility fracture. Patients who were fifty years of age or older and were hospitalized for the treatment of a fragility fracture at either of two academic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
0
30
0
2
Order By: Relevance
“…Entscheidend ist neben der chirurgischen Versorgung von Fragilitätsfrakturen somit aber auch die Einleitung einer weiterführende Sekundärprophylaxe, da das Vorliegen dieser Frakturen der stärkste Risikofaktor für die Entstehung weiterer Frakturen ist [3,22]. Die Abklärung und ggf.…”
Section: Therapieunclassified
See 1 more Smart Citation
“…Entscheidend ist neben der chirurgischen Versorgung von Fragilitätsfrakturen somit aber auch die Einleitung einer weiterführende Sekundärprophylaxe, da das Vorliegen dieser Frakturen der stärkste Risikofaktor für die Entstehung weiterer Frakturen ist [3,22]. Die Abklärung und ggf.…”
Section: Therapieunclassified
“…Nach wie vor erhalten nur etwa 11-16 % aller Frauen und nur 3,4 % aller Männer mit Osteoporose eine adäquate Therapie [17]. Nach einer Studie von Edwards et al [3] erhöht die Empfehlung einer Osteoporosetherapie durch den Unfallchirurgen an den nachbehandelnden Arzt bereits die Therapieraten. Wenn jedoch die Osteoporosetherapie gleich während der Behandlung im Krankenhaus initiiert wird, sind die Complianceraten signifikant höher.…”
Section: Therapieunclassified
“…The PQRS currently assesses the appropriate treatment of osteoporotic individuals, among other measures, and passes that information on to CMS to use as a determination of health care reimbursement rates [61]. It has also been suggested that soon the Joint Commission will be using similar quality measures during its assessment of hospitals for accreditation [23].…”
Section: What Happens To Patients That I Refer For Evaluation?mentioning
confidence: 99%
“…The presence of fragility fractures should lead to the consideration of treatment or at least exploration of bone metabolism. The orthopaedic surgeon is routinely involved in cases of fragility fractures, and many studies have shown that early osteoporosis screening by the orthopaedic surgeon, as part of the treatment plan, leads to better disease management [3,[22][23][24][25]. Orthopaedic surgeons are typically only involved in the osteoporotic patient's care as a consequence of a fracture and with the single biggest risk factor for a future fracture being a previous fragility fracture, it therefore follows that the area of focus for the orthopaedist should be on the secondary prevention of future fractures [4,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation